The effect of L-Arginine on Ciliary Beat Frequency in PCD patients, non-PCD respiratory patients and healthy controls - Kouis, Panayiotis; Hadjisavvas, Andreas; Middleton, Nicos; Papatheodorou, Stefania; Kyriacou, Kyriacos; Yiallouros, Panayiotis K. (My University, 2018)
Objectives Few studies have examined the potentially therapeutic effect of increasing the production of endogenous nitric oxide (NO) in Primary Ciliary Dyskinesia (PCD) and other chronic respiratory conditions. Nasal NO is low in PCD and has been found to correlate with compromised Ciliary Beat Frequency (CBF). In this study we assessed the effect of increasing L-Arginine, as the substrate of NO synthases, on CBF in biopsies of human respiratory ciliated epithelium. Methodology A total of 28 suspect cases with chronic respiratory manifestations referred for PCD diagnostic testing and 8 healthy controls underwent nasal brushing. Obtained epithelial cells were divided between three culture medium 199 solutions, containing different levels of L-Arginine (0.33 mM as baseline, 1 mM and 10 Mm as increased levels). CBF measurements were obtained at 37 °C and 25 °C at 1, 3 and 24 h after sample acquisition. Results Among a total of 36 recruited subjects, 8 had PCD confirmed (PCD n = 8), 20 had PCD excluded (non-PCD n = 20) and 8 were healthy controls (Healthy Controls = 8). Among PCD subjects, ciliary motility was characterized by rotational (n = 5) or dyskinetic (n = 3) beating. At 37 °C, compared to baseline, higher levels of L-Arginine resulted in up to 9% CBF increase at 1 h (p = 0.007), up to 9% CBF increase at 3 h (p < 0.001) and up to 12% CBF increase at 24 h (p = 0.002). Similar although smaller scale increases were recorded at 25 °C. The effect of L-Arginine was time dependent (interaction p = 0.002) and was similar in PCD patients, non-PCD chronic respiratory patients and healthy controls (interaction p = 0.800). Conclusions L-Arginine increases CBF and merits to be evaluated as a potential stimulator of mucociliary clearance in chronic respiratory conditions and congenital ciliary disorders with residual motility. Larger human studies are needed to confirm these findings.
Keywords: Ciliary motility; L-Arginine; Nitric oxide; Primary Ciliary Dyskinesia